Management and outcome of pregnancies in women with red cell isoimmunization: a 15-year observational study from a tertiary care university hospital - María Ángeles Sánchez-Durán; María Teresa Higueras; Cecilia Halajdian-Madrid; Mayte Avilés García; Andrea Bernabeu-García; Nerea Maiz; Nuria Nogués; Elena Carreras (BMC, 2019)
Abstract Background The aims of this study were to determine the prevalence of the different anti-erythrocytic alloantibodies, to describe pregnancy outcomes according to a low-risk and high-risk classification for fetal anemia and to determine the factors that influence adverse perinatal outcomes. Methods This retrospective observational study included women referred to our center following the identification of maternal anti-erythrocytic alloantibodies between 2002 and 2017. Pregnancies were classified as high risk for fetal anemia in cases with clinically significant antibodies, no fetal-maternal compatibility and titers ≥1:16 or any titration in cases of Kell system incompatibility. In high-risk pregnancies, maternal antibody titration and the fetal middle cerebral artery peak systolic velocity (MCA-PSV) were monitored. Low-risk pregnancies underwent routine pregnancy follow-up. Results Maternal antibodies were found in 337 pregnancies, and 259 (76.9%) of these antibodies were clinically significant. The most frequent antibodies were anti-D (53%) and anti-K (19%). One hundred forty-three pregnancies were classified as low risk for fetal anemia, 65 (25%) cases were classified as no fetal-maternal incompatibility, 78 had clinically nonsignificant antibodies, 4 (2.8%) resulted in first-trimester pregnancy loss, and 139 (97.2%) resulted in livebirths. Of the 194 high-risk pregnancies, 38 had titers < 1:16 (resulting in 38 livebirths), and 156 had titers ≥1:16 or anti-K antibodies. In the last group, 6 cases miscarried before 18 weeks, 93 had a MCA-PSV < 1.5 multiples of the median (MoM), resulting in 3 perinatal deaths that were unrelated to fetal anemia, one termination and 89 livebirths; and 57 had a MCA-PSV > 1.5 MoM, resulting in 3 intrauterine deaths, 6 terminations and 48 livebirths. Ninety-two intrauterine transfusions were performed in 45 fetuses (87% anti-D). Adverse outcomes were related to a MCA-PSV > 1.5 MoM (p < 0.001), hydrops (p < 0.001) and early gestational age at first transfusion (p = 0.029) Conclusion Anti-D remains the most common antibody in fetuses requiring intrauterine transfusion. A low or high-risk classification for fetal anemia based on the type of antibody, paternal phenotype and fetal antigen allows follow-up of the pregnancy accordingly, with good perinatal outcomes in the low-risk group. In the high-risk group, adverse perinatal outcomes are related to high MCA-PSV, hydrops and early gestational age at first transfusion.